Digital and Local Potential-Based Tourism Village Development Strategy with Pentahelix Approach in Realizing Sustainable Tourism - Helita, Widia; Fitriyah, Hadiah (CV. Media Digital Publikasi Indonesia, 2025)
The implementation of Law No. 12/2008 on Local Government has provided opportunities for local governments to manage and optimize the potential of their regions independently, including managing the tourism sector. Tourism village development is a planned change that requires the participation of local communities in a holistic manner. Sustaniable development has become a global agenda in every development process. Therefore, all stakeholders including the government in various development sectors must apply the principles of sustainable development in every policy and development plan that will be implemented. In the Digital-Based Tourism Village Development Strategy and Local Potential in Realizing Sustainable Tourism in Sidoarjo Regency, the author will use descriptive qualitative research methods with a pentahelix approach.